Spatial modeling of Geomorphotectonic in Zawa Mountain (Journal of the College of Basic Education, 2022)
This paper deals with the study of Zawa Mountain which is located in the north Iraq by performing a model for the geomorphotectonic hazards based on the geomorphological and tectonic indications, besides using GIS techniques in order to find the spatial relation of these indicators. Different layers were created for these indicators then were joined to compile the spatial map of the distribution of geomorphotectonic hazards at Zawa Mountain. The hazards were divided into five classes and it was found that (40.75 %) of the research area is located in Medium Hazard areas, then (32.08%) Low Hazard areas, (10.94%) Hazard areas, and (0.45%) Extremely High Hazard area, whereas only (15.85%)of the research area is free from hazards. It was found that the tectonic origin represented by tectonic activities and their role in the development of faults, lineaments, and seismic activity,all were contributed in forming the geomorphological characteristics; accordingly, formed unstable slopes in the research area